Sequencing, cloning and high-yield expression of a fungal β-N-acetylhexosaminidase in Pichia pastoris - Slámová, Kristýna; Bojarová, Pavla; Gerstorferová, Daniela; Fliedrová, Barbora; Hofmeisterová, Jana; Fiala, Martin; Pompach, Petr; Křen, Vladimír (Protein expression and purification, 2012)
The β-N-acetylhexosaminidase from Talaromyces flavus has a remarkable synthetic ability, processing even carbohydrates with various functionalities. Its broader use is partially hampered by low-yield production in the native fungus. Here, we present an optimized 3-day production of this enzyme in the eukaryotic host of Pichia pastoris, in ca 10-fold higher volume activity (10 U/ml) and close-to-perfect purity (one chromatographic step needed). Importantly, the recombinant enzyme features the same biochemical and catalytic properties, including the syntheses with derivatized carbohydrate substrates. This is the first example of the overexpression of a fungal β-N-acetylhexosaminidase by a single-cell producer in liquid medium. It represents a promising solution for wider biotechnological applications of this outstanding enzyme.
Keywords: Sequence Analysis, DNA; exprese genu; beta-N-acetylhexosaminidasy; klonování DNA; beta-N-Acetylhexosaminidases; rekombinantní proteiny; sekvenční analýza DNA; DNA, Complementary; Recombinant Proteins; Pichia; Cloning, Molecular; komplementární DNA; Talaromyces; Gene Expression